IMPACT OF PHARMACIST LED ANTICOAGULATION MONITORING AND PATIENT EDUCATION ON ORAL ANTICOAGULATION THERAPY WITH ACENOCOUMAROL - CHEDEPUDI, Poojitha Reddy; Mounika, Omsri; Chandrika, Gaddam; Franklin, Aldrich; M, Ramesh; Rani N, Vanitha; P, Thennarasu (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objective: Acenocoumarol is anoral anticoagulant with narrow therapeutic index, and the ideal dose of anticoagulation lies between International normalized ratio (INR) values of 2.0 and 3.5. Lack of monitoring and knowledge on acenocoumarol therapy may compromise patient's safety resulting in under- or over-anticoagulation. A study was conducted to monitor for the safety of anticoagulation therapy, achievement of goal INR levels and to assess the impact of pharmacist led anticoagulation monitoring and patient education on the rational use of acenocoumarol in patients admitted in cardiology wards with thromboembolic disorders. Methods: The study was conducted in 70 patients; data collection was done, prescriptions were analyzed for drug-drug interactions and adverse drug reactions (ADRs). Patients' knowledge on acenocoumarol therapy was assessed using a self-developed questionnaire at the baseline, then were subjected to a detailed patient education and on an average each patient received three sessions of education. They were again made to answer the same questionnaire on the day of discharge. The mean score of the responses before and after education was compared statistically using Wilcoxon signed rank test and McNemar test. Results: There were 60% patients under anticoagulated with the INR range of >2.0. 123 drug interactions were observed in 58 patients, on an average of 2 interactions per prescription, but no ADRs were observed. 59 patients (84.3%) showed significant overall improvement in knowledge on anticoagulation therapy following education. Conclusion: This study implies the role of clinical pharmacists in achieving better clinical outcomes in patients receiving oral anticoagulation therapy with acenocoumarol.